Structural Performance Analysis of the Classroom Building at the South Minahasa Marine Training and Education Center Using the Pushover Method - Femmy The; Steenie E. Wallah; Marthin D. J. Sumayouw (Journal of Engineering, Electrical and Informatics, 2025)
Minahasa Selatan is a region with high seismic activity, requiring accurate structural design and evaluation against earthquake loads. This study aims to evaluate the seismic performance of a classroom building at the Marine Training and Education Center in Minahasa Selatan using the pushover method within a performance-based seismic design approach. The main issue addressed is how different response spectra—SNI 1726:2019 and the Indonesian Design Spectrum—affect structural performance assessment. The methodology includes literature review, structural modeling based on Asbuilt Drawings, and pushover analysis using SAP2000 software, referencing FEMA-356, FEMA-440, and ATC-40 guidelines. Results indicate that the SNI 1726:2019 spectrum yields higher shear forces and displacements compared to the Indonesian Design Spectrum, though the difference remains below 3%. Maximum shear force reaches 19,716.449 kN and displacement is 0.173 m (FEMA-440), while ATC-40 yields a minimum displacement of 0.1456 m and base shear of 3985.007 kN. The analysis places the structure within the Life Safety (LS) to Collapse Prevention (CP) performance range, suggesting it can maintain global stability and protect occupants during seismic events despite reduced stiffness. The study concludes that the building remains structurally safe and functionally adequate after an earthquake, and that variations in the response spectra result in limited impact on performance evaluation outcomes.